Anthropometric profile and physical performance characteristic of the Brazilian amputee football (soccer) team - Mário A. M. Simim; Bruno V. C. Silva; Moacir Marocolo Júnior; Edmar L. Mendes; Marco T. de Mello; Gustavo R. da Mota (Universidade Estadual Paulista (UNESP), 2013)
Amputee football is a variation of conventional soccer in which athletes with lower limb amputation and one athelete with upper limb amputation (the goalkeeper) participate. The objective of this study was to investigate the anthropometric and physical characteristics of amputee football athletes and to verify differences between heart rate peak (HRpeak) and equations for predicting maximum heart rate (HRmax). Twelve amputee soccer players from the Brazilian team participated in this study. The body mass, height and body composition were measured. The physical tests used were: the 20 m running test, the T-square test and the Yo Yo intermitent recovery test - level 1 (YYIRT1). The percentage of fat was significantly different between midfielders and defenders. No significant differences were found between positions in the physical tests. The HRpeak was significantly lower than all of HRmax prediction equations tested. We conclude that the indicators of physical performance did not differ significantly between the different tactics roles of players, and that, after intermittent maximum effort, the cardiac response was lower when compared with the investigated HRmax prediction equations.